AB0428 ASSOCIATION BETWEEN GEOGRAPHIC AND CLIMATOLOGICAL CONDITIONS AND CUTANEOUS MANIFESTATIONS IN LUPUS PATIENTS FROM THE SPANISH RHEUMATOLOGY SOCIETY LUPUS REGISTRY (RELESSER) AND ARGENTINE RHEUMATOLOGY SOCIETY LUPUS REGISTRY (RELESSAR) COHORT. (2nd June 2020) - Menor-Almagro, R.; Argentina García, M.; Rua-Figueroa, I.; Pons Estel, G.; Martin-Martinez, M. A.; Muñoz Jimenez, A.; Galindo-Izquierdo, M.; Calvo-Alen, J.; Fernandez-Nebro, A.; Olive, A.; Pons-Estel, B.; Pego-Reigosa, J. M.
Abstract : Background: Climatological conditions and ethnicity impact on the course of the disease in systemic lupus erythematosus patients. Objectives: We carry out a study to analyze cutaneous manifestations in SLE patients from Argentina and Spain. Methods: Patients data from Spanish Rheumatology Society Lupus Registry (RELESSER) and Argentina Rheumatology Society Lupus Registry (RELESSAR) were retrospectively analyzed for presence of cutaneous lesions (alopecia, photosensitivity, malar rash, discoid lesions, oral ulcers and subacute lesions). RELESSER-T and RELESSAR-T are multicenter, hospital-based registries, with retrospective cross-sectional collection of data about patients with SLE attending Spanish and Argentinian rheumatology services from the public national health system. Data about climatological conditions throughout the Spanish and Argentinian geography were provided by the Spanish Meteorological Agency and Argentine Meteorological Services. Results: A total of 5604 patients were included, median age 44.6 ± 15.3, 90.4 % female. Current smokers were 28, 9%. Other climatological, geographical, biological and clinical data are shown in table 1 . In the multivariable model, the presence of cutaneous lesion were significantly associated with temperature OR 1.116 (95% CI:1.042-1.196 p=0, 002), altitude OR 1.001 (95% CI:1.000-1.001, p=0.012), hemolytic anemia OR 1.401 (95% CI:1.017-1.931 p=0.039) and serositis OR 1.509 (95% CI:1.215-1.875 p=0.000). Negative associations were observed between females OR 0.392 (95% CI:0.297-0.518, p=0.000), latitude OR 0.994 (95% CI:0.988-0.999, p=0.000), oceanic climate OR 0.566 (95% CI:0.381-0.842, p=0.005), leukopenia OR 0.790 (95% CI:0.643-0.970, p=0.025), renal disorder OR 0.761 (95% CI:0.600-0.966, p=0.025), glucocorticoids treatment OR 0.571 (95% CI:0.456-0.715, p=0.000) and antimalarial drugs OR 0.439 (95% CI:0.342-0.563, p=0.000). Conclusion: In the current analysis, taking RELESSAR and RELESSER data together, we observe positive association between higher temperature and skin lesion and negative association with living in southern hemisphere latitudes. References: Influence of Solar Radiation in Cutaneous Manifestations of Lupus: Data from the Gladel Cohort [abstract]. Arthritis Rheumatol. 2016; 68 (suppl 10). Disclosure of Interests: Raúl Menor-Almagro: None declared, Mercedes Argentina García: None declared, Iñigo Rua-Figueroa: None declared, Guillermo Pons Estel: None declared, Maria Auxiliadora Martin-Martinez: None declared, Alejandro Muñoz Jimenez.: None declared, María Galindo-Izquierdo: None declared, Jaime Calvo-Alen: None declared, Antonio Fernandez-Nebro: None declared, Alejandro Olive: None declared, Bernardo Pons-Estel Grant/research support from: GSK, Janssen, Consultant of: GSK, Janssen, Speakers bureau: GSK, Janssen, Jose M Pego-Reigosa: None declared